Pengaruh Profitabilitas, Free Cash Flow, Likuiditas Dan Pertumbuhan Penjualan Terhadap Kebijakan Hutang Pada Perusahaan Sektor Industri Barang Konsumsi Yang Terdaftar Di Bursa Efek Indonesia Periode 2016-2019 - Bartholomeus Nainggolan; Resi Agustina Manalu; Ferdinand Napitupulu (Journal of Economic, Bussines and Accounting (COSTING), 2021)
This research was conducted to see the effect of profitability, free cash flow, liquidity and sales growth on debt policy. This research was conducted in consumer goods industry sector companies listed on the IDX with a population of 52 in 2016-2019. The sampling method used in this study was purposive sampling technique so that a sample of 31 companies was obtained. The analysis technique used is multiple linear regression. Based on the results of the research carried out, it can be seen that the liquidity variable partially has a negative and significant effect on debt policy. The variables of profitability, free cash flow and sales growth partially have no effect and are not significant to the debt policy. Simultaneously, the variables of profitability, free cash flow, liquidity and sales growth have a significant effect on debt policy. Keywords: Profitability, Free Cash Flow, Liquidity, Sales Growth, Debt Policy